Balloon pulmonary angioplasty followed by pulmonary endarterectomy: Combination treatment for high-surgical-risk patients with chronic thromboembolic pulmonary hypertension. Issue 3 (24th February 2023) - Shimahara, Yusuke; Suzuki, Shun; Fujiyoshi, Toshiki; Honda, Sayaka; Koizumi, Nobusato; Yamashita, Jun; Sasaki, Yuichi; Ito, Ryosuke; Takahashi, Lisa; Nakai, Michikazu; Ogino, Hitoshi
Abstract: OBJECTIVES: Our goal was to evaluate the combined effects of balloon pulmonary angioplasty (BPA) followed by pulmonary endarterectomy (PEA) to treat high-surgical-risk patients with chronic thromboembolic pulmonary hypertension (CTEPH). METHODS: This study included 58 patients with CTEPH who had pulmonary vascular resistance of ≥1000 dyn·s/cm 5, mean pulmonary arterial pressure (mPAP) of ≥45 mmHg or mPAP of 38–44 mmHg with comorbidities. Of these, 21 patients underwent the combined therapy of BPA followed by PEA (BPA group) and 37 underwent direct PEA (non-BPA group). Preoperative and postoperative results were compared between the 2 groups. An early postoperative composite event comprised the postoperative use of extracorporeal membrane oxygenation or intra-aortic balloon pump, in-hospital death, rescue BPA, prolonged ventilation, tracheostomy, prolonged stay in the intensive care unit, deep sternal wound infection and cerebral infarction. RESULTS: Before the first intervention (before BPA or direct PEA), patients in the BPA group had a higher mPAP than those in the non-BPA group. After undergoing BPA before PEA, the BPA group demonstrated significantly decreased mPAP and pulmonary vascular resistance (43 vs 52 mmHg, P  < 0.001; 636 vs 965 dyn·s/cm 5, P  = 0.003, respectively) and significantly increased cardiac output (4.1 vs 3.5 l/min, P  = 0.041). Notably, the number of patients with the early postoperative composite event was significantly lower in the BPA group than in the non-BPA group (4.8% vs 35.1%, P  = 0.011). CONCLUSIONS: Compared with direct PEA, the combination therapy of BPA followed by PEA can be a feasible and effective risk-reduction strategy for high-surgical-risk patients with CTEPH. Abstract : Pulmonary endarterectomy (PEA) is considered the first-line therapy in the treatment algorithm for chronic thromboembolic pulmonary hypertension (CTEPH) [1, 2].